Biphyllidae (Coleoptera, Cucujoidea) – a new beetle family to the fauna of Kazakhstan - Izbasar I. Temreshev (Acta Biologica Sibirica, 2024)
False skin beetle Biphyllus lunatus (Fabricius, 1787) is firstly recorded from Kazakhstan. The finds of B. lunatus from Ulytau Oblast of Central Kazakhstan are currently the easthmost localities for this species and first record for Central Asia. The records of the beetles from family Biphyllidae were absent for Kazakhstan.